Neuroprotective effects of sea buckthorn leaf extract against hypobaric hypoxia and post-hypoxic reoxygenation induced hippocampal damage in rats. - Iswar Baitharu; Satya Narayan Deep; Govindasamy Ilavazhagan (International Journal of Phytomedicine, 2016)
Exposure to hypobaric hypoxia (HBH) and reoxygenation (H/R) causes hippocampal neuronal damage leading to memory dysfunction and mood state alteration. The present study aimed at investigating the potential neuroprotective effect of seabuckthorn leaf extract ((SBTLE)) against HBH and reoxygenation induced neuronal injury in brain. Six groups of male sprague dawley rats were taken and exposed to simulated HBH equivalent at an altitude of 7600m in an animal decompression chamber for 7 days followed by reoxygenation. Rats were supplemented with SBTLE (100mg/kgBW) 20 days prior and during hypoxic exposure. Recovery from injuries following HBH exposure and subsequent reoxygenation was carried out in separate group of animals. Our study revealed that exposure to reoxygenation stress following hypoxia enhanced hypoxia induced oxidative stress in hippocampal neurons which was reversed with SBTLE supplementation. SBTLE restored Hypoxia/Reoxygenation(H/R) induced downregulation of γ-glutamylcysteine synthetase (GCLC) enzymes responsible for glutathione biosynthesis. Post hypoxic supplementation of SBTLE decreased the reoxygenation induced enhanced oxidative markers, however, administration of SBTLE in conjunction with the inhibitor of GCLC resulted in slow recovery from H/R injuries. These results provide the first evidence of SBTLE induced increase in glutathione biosynthesis by upregulating GCLC enzyme expression and hence can be used as a promising drug to cure H/R induced neuronal damages.